Estudio morfológico de Smilax L. (Smilacaceae) en Costa Rica, con implicaciones sistemáticas - Ferrufino Acosta, Lilian; Gómez-Laurito, Jorge (Lankesteriana: International Journal on Orchidology, 2016)
A morphologic revision of Costa Rican species of Smilax is presented. Traditionally, up to 14 species were accepted. In the present paper 7 species are recognized: Smilax domingensis, S. mollis, S. pana- mensis, S. spinosa, S. spissa, S. subpubescens, and S. vanilliodora. The following names are treated as synonyms: Smilax engleriana and S. kunthii of S. domingensis; S. hirsutior, S. angustiflora and S. candelariae of S. mollis, and S. chiriquensis and S. regelii var. albida of S. vanilliodora. Smilax regelii is excluded as a valid taxon and a lectotype of S. gymnopoda is designated. Dichotomous keys with vegetatives and reproduc- tive characters (flowers and fruits) are presented, on the basis of field and herbaria observations. For all the species many important characters useful for identification were included, such as rhizome, stem, size of tepals and variation in berry colour during development stages.